Hapteo: Sharing visual-haptic experiences from virtual environments - Yongyao Yan; Ruthenbeck, Greg S.; Reynolds, Karen J. (IEEE Haptics Symposium, 2014)
For over two decades, haptics has provided people with new computer interaction styles across a range of applications. However, it is difficult to share haptic experiences and compare haptic rendering algorithms. In this paper, we introduce a new system called Hapteo that enables "haptic videos" (videos with haptic recordings) to be recorded and replayed without requiring haptic virtual environment software to be deployed. Our system enables users to capture visual-haptic information easily and share it using the Hapteo Player. In order to provide a more realistic and interactive experience, contact surfaces and haptic forces are modeled with radial basis functions, and videos are replayed in a haptic-driven style.